PENGARUH FASILITAS KERJA, DISIPLIN KERJA, DAN MOTIVASI KERJA TERHADAP KEPUASAN KARYAWAN DI PT. GRIYA NUTRISI - Mahirah, Nadhya Husna; Siddiq, Andhika Mochamad; Muttaqin, Ridlwan (Ikatan Sarjana Ekonomi Indonesia Cabang Pekanbaru, 2024)
Analyzing the impact of work facilities, work discipline, and work motivation on employee satisfaction at PT Griya Nutrisi is the purpose of the study that conducted. Forty-five workers of PT Griya Nutrisi participated in the survey, which was conducted using a quantitative research methodology. Testing validity, reliability, multiple linear regression analysis, and hypothesis testing are all part of data analysis procedures. Results, employee happiness is significantly impacted by work facilities, work discipline, and work incentive all at the same time. Each of these factors also significantly improves employee happiness, to a certain extent. Keywords: Work Facilities, Work Discipline, Work Motivation, Employee Satisfaction